(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2019)
Acetylcholinesterase is an important enzyme in biosensing works. It is utilized to detect insecticides and cheaper sources of the enzyme is constantly being sought. Optimisation of the acetylcholinesterase extraction from the brain of Clarias batrachus using Response Surface Methodology is reported for the first time in this study. AChE from the brain of this fish was extracted and partially purified using ammonium sulphate. The optimum range of ammonium sulphate cut was between 40 and 50%. RSM was conducted using Box-Behnken design and the optimisation value for the extraction was determined for each variable at the end of the study. The optimum concentrations of Triton X-100, PMSF, phosphate buffer and the pH for AChE extraction based on RSM were 0.75%, 1.00 mM, 0.075 M and 7.5, respectively.